Cold room design / Mohd Nuh Miskan - Miskan, Mohd Nuh (2004)
In this thesis, chapter 1 addresses the introduction to the project. It deals with the energy efficiency and energy analysis. Apart from that, the objectives of this project are described as well as the scope of project. Chapter 2 includes the methodology of the project. Chapter 3 introduces the important of proper storage in order to maintain the freshness of product. The theory of refrigeration cycle is presented in chapter 4. All the theories are based on the thermodynamics and heat transfer point of view. Chapter 5 and will describe the refrigeration load calculation. Chapter 6 , 7 and 8 will describe three major parts in basic refrigeration cycle which is evaporator, compressor and condenser respectively. The reason of selecting the Ammonia as working fluid in this thesis will explain in chapter 9. The analysis of existing cold room in FAMA is described in chapter 10. The discussion, conclusion and recommendation are imparted in chapter 11, 12 and 13 respectively.